Oral health and related factors in a group of children with cystic fibrosis in Istanbul, Turkey - YARAT, AYŞEN; KARGÜL, BETÜL; PEKER, MEHMET SERTAÇ; AKBAY, TUĞBA (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2015)
Background: Cystic fibrosis (CF) patients can be considered as high caries risk patients because they frequently consume sugar-rich food between meals and they have a high intake of sugar containing syrups, aerosols, and salivary flow reducing medication. Variable caries prevalences were reported in CF patients in previous studies. There are no studies related to CF and salivary thromboplastic activity, which can be presented as a marker of wound healing and bleeding tendency of oral cavity. Objective: The aim of this study was to compare oral health status and salivary pH, flow rate, and thromboplastic activity in children with CF and healthy controls. Materials and Methods: A sample of 35 children with CF (23 girls and 12 boys), and 12 healthy control subjects (6 girls and 6 boys) were selected. Caries experience, oral hygiene, and dental erosion were assessed. Salivary flow rate, pH, thromboplastic activity, and total protein content were determined. Differences between the groups were evaluated using Chi-square test with a significance level set at 0.05. Results: The differences between children with CF and healthy controls in tooth brushing frequency, use of fluoride tablets, caries experience, dental erosion index, oral hygiene index, salivary flow rate and total protein levels were not statistically significant (P > 0.05). Salivary thromboplastic activity of the CF group was significantly lower than the healthy controls (P < 0.01). Conclusion: Large population studies may be necessary to establish the role of salivary thromboplastic activity in children with CF considering our findings related to the decreased salivary thromboplastic activity, which may indicate delayed oral wound healing process.
Keywords: Caries; children; cystic fibrosis; saliva; salivary thromboplastic activity; TISSUE FACTOR; SALIVA